2020
DOI: 10.5755/j01.ms.26.4.23053
|View full text |Cite
|
Sign up to set email alerts
|

Heat Behavior of Electrically Conductive Concretes with and without Rebar Reinforcement

Abstract: Lately, electrically conductive concrete (ECC) is being investigated to prevent accumulation of snow and ice. The conductivity of electrical conductive concretes containing steel fiber is reduced by the corrosion of the steel fiber in time. Therefore, it is proposed to produce electrical conductive concretes that does not contain steel fibers recently. In this study, it is aimed to examine rebars in electrical conductive concretes non containing steel fiber. For this, 45 ´ 45 ´ 5 cm ECC slabs with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…In these studies, the four-probe technique or other superficial test techniques are used as the measurement method. Since the resistivity measurement reason in the current study was to specify the bulk conductivity of the samples, the two-point uniaxial measurement method, which is also frequently used in the literature [21,28], was preferred. A potential difference of 40 volts was applied to all samples for resistivity measurement.…”
Section: Test Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, the four-probe technique or other superficial test techniques are used as the measurement method. Since the resistivity measurement reason in the current study was to specify the bulk conductivity of the samples, the two-point uniaxial measurement method, which is also frequently used in the literature [21,28], was preferred. A potential difference of 40 volts was applied to all samples for resistivity measurement.…”
Section: Test Methodsmentioning
confidence: 99%
“…While the electrical resistivity of outdoor dried concrete was determined as 6.54 X 10 5 -11.4 X 10 5 Ω.cm, the electrical resistivity of saturated concrete and dry concrete were determined to be 10 6 Ω.cm and 10 9 Ω.cm, respectively [21]. The specification of a conductivity class for concretes may vary for different purposes.…”
Section: Electrical Resistivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of electrolytic additives effects the structure formation, and changes the dispersion, quantity, and shape of hydrates [33][34][35]. In a number of studies [36,37], it was found that the use of an electrolyte such as calcium nitrate reduces the degree of structure crystallization of concrete in the long term due to the interaction of nitric acid salt with aluminum-containing phases of Portland cement forming calcium hydronitroaluminates and calcium hydroxynitrates.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive concrete methods are to mix the appropriate amount of steel fiber [10], carbon fiber [11,12] or graphene into concrete [13]; in this way, the concrete can have a certain electrical resistance so that the concrete can produce heat to melt ice and snow after being electrified. However, the doped materials are prone to corrosion in concrete, resulting in the decrease of electrical and thermal efficiency [14].…”
Section: Introductionmentioning
confidence: 99%